Comprehensive evaluation of the color-leaf plants introduced in Northern Anhui based on analytic hierarchy process - ZHANG Xiaowei; GONG Xuemei; LI Lin; ZHOU Zhixiang; LIU Dan (浙江大学学报. 农业与生命科学版)
By field investigation of introduced color-leaf plants, we chose 43 main kinds of color-leaf plants in Northern Anhui as the research objects, which including Acer saccharum, Photinia fraseri, Prunus persica ‘Atropurpurea’, Aucuba japonica var. variegata, Ligustrum vicaryi, etc. In the premise of sufficiently considering the biological characteristics, ecological adaptability and ornamental feature, a comprehensive evaluation model of color-leaf plants was established by using the analytic hierarchy process to evaluate the 43 kinds of color-leaf plants in Northern Anhui with specific evaluation indexes and scoring criteria. As indicated by the weight value of standard layer in the comprehensive evaluation model, color duration, leaf color and cold resistance are important factors to evaluate introduced color-leaf plants. The plants were divided into four grades according to the scores, among which, the 13 species had the highest application value, such as Acer negundo ‘Aurea’, etc; the 16 species had the higher application value, such as Aucuba japonica var. variegata, etc; the 11 species had common application value, such as Acer saccharum, etc; the rest 3 species had lower application value, such as Pyracantha fortuneana ‘Harlequin’, etc. This study provides a reference for rational development and application of these introduced color-leaf plants in Northern Anhui Province.